REPRESENTATION OF THE ELDERLY PROTAGONIST IN TRACY LETTS’ AUGUST: OSAGE COUNTY - Gaidash, A. (Studia Philologica, 2019)
This article examines the literary portrayal of the female sexagenarian in the Pulitzer-Prize winning play. The gerontological portrait of the elderly is analyzed in the context of “the young old” adults. The theoretical background of the article is formed from an array of humanities-related disciplines: in particular, sociology, literary gerontology, medical humanities. The author of the article studies how the notion of normativity in late adulthood is represented in August: Osage County. The playwright subverts the concepts of successful and healthy aging in the images of Violet and Beverly Westons: Violet is a heavy smoker; Beverly is a heavy drinker. The issue of ableism allows us to detect the element of a new genre of pathography, a battle, which is indicative of the gerontological portrayal of the elderly protagonist. In his drama, Tracy Letts develops active and passive strategies of aging, which his elderly characters choose to cope with their disabilities in late adulthood.